Strategi Pengembangan Madrasah Aliyah Untuk Mencapai Kategori Sekolah Unggul - Lula Leo Nyta; Awang Kustiawan; Dadi Dadi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
Madrasas have a dual role, namely as a place to gain knowledge and form the character of akhlakul karimah. Madrasas also remain in the main challenge to always improve quality institutionally through developing madrasas into quality educational institutions. This study seeks to describe the implementation of quality development strategies at MAN 1 Ciamis and MAN 2 Ciamis. The study used a qualitative descriptive method with the research subjects being the Head of Madrasah, Deputy Head of Madrasah, Teachers, and Students. To obtain data used techniques of observation, interviews, and documentation studies. The collected data were analyzed through data reduction, data presentation, drawing conclusions, and triangulation. The results of the study show that the implementation of the development strategy carried out by MAN 1 Ciamis and MAN 2 Ciamis are: 1) development of superior programs according to the characteristics of madrasas; 2) student program by selecting the acceptance of new students and the development of talent interests; 3) human resource development program with attention to HR recruitment and competency development through training; 4) infrastructure development program to support learning activities.